The first Cretaceous ophiopluteus skeleton (Echinodermata: Ophiuroidea). (November 2021) - Reich, Mike
Abstract: Larvae of sea urchins, brittle stars, and allies are common, ecologically important, and diverse members of marine ecosystems in all of the world's oceans today. In contrast to modern representatives, the fossil record of echinoderm larvae is poorly known. This study reports the first ophiopluteus skeleton from Cretaceous sediments worldwide, obtained from chalky sediment of the Isle of Wolin, NW Poland. The evidence presented here, that it is possible to isolate fossil echinoderm larval skeletons from rocks, indicates a hidden diversity of such fragile fossils and thus the possibility of direct geological recording.